Pengaruh Gaya Kepemimpinan Transformasional Kepala Sekolah, Organizational Citizenship Behavior Dan Komitmen Organisasional Terhadap Kepuasan Kerja - Waimbo, Anton (Universitas Sam Ratulangi, 1996)
The results of this research showed that in partial Transformational Leadership Style Principal (X1) is not significant effect on job satisfaction variable (Y). Variable Organizational Citizenship Behavior (X2) is not significant effect on job satisfaction variable (Y). Organizational Commitment variable (X3) is significant positive effect on job satisfaction variable (Y). From the results of the regression analysis as described above showed that two variables (Principal Transformational Leadership Style and Organizational Citizenship Behavior) has no significant effect on job satisfaction. While one variable that organizational commitment has significant influence on satisfaction Work Keywords: Transformational Leadership Style, Organizational Citizenship Behavior, Organizational Commitment, Job Satisfaction